Competitive Strategies of Regional Development Banks: The Role of Intellectual Capital, Organizational Capability, and Governance Risk Compliance - Prakoso, Roy; Widyastuti, Sri; Gustari, Irvandi (Dinasti Publisher, 2025)
The development of the banking industry in today's digital era highlights the importance of Regional Development Banks (BPD) and stakeholders in taking strategic steps to remain competitive and provide the best services, particularly in contributing to Regional Original Revenue (PAD). This study aims to analyze the factors influencing the competitiveness of Regional Development Banks (BPD) in the Sumatra region, such as intellectual capital, organizational capability, and Governance Risk Management Compliance (GRC). The research adopts a quantitative approach using the SEM-PLS method and involves 60 respondents from eight BPDs operating in Sumatra. The findings indicate that intellectual capital, organizational capability, and GRC positively influence Sustainable Competitive Advantage (SCA), both directly and through bank performance as an intervening variable. Additionally, financial performance as an independent variable also shows a significant positive impact on SCA